Analisis Kinerja Panitia Pemungutan Suara (PPS) Dalam Pemutakhiran Data Pemilih Untuk Mewujudkan DPT yang Akurat Desa Tempuran Kecamatan Bantaran Kabupaten Probolinggo - Andhi Nur Rahmadi; Diki Wahyudi; Achmad Dany Agustyan; Hendrik Andrianto Indria (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The process of updating voter data is a critical step in organizing elections, considering that an accurate Permanent Voter List (DPT) serves as the foundation for the validity of election results. This study was conducted to examine the performance of the Village Voting Committee (PPS) at the village level, specifically in Tempuran Village, in the context of data updating with the perspective of Good Governance principles, namely Effectiveness and Equality. The research method used is descriptive qualitative, with data obtained from in-depth interviews, direct field observations, and studies of related documents. The study results show that the PPS has worked through planned procedures, including the recruitment process, inter-party coordination, checking and listing activities (coklit), compilation of the Provisional Voter List (DPS), determination of the DPT, as well as supervisory duties during voting and vote counting. Analysis based on Grindle's theory indicates that although the institutional and administrative capacity of the PPS is quite good, its level of effectiveness still faces challenges such as variations in human resource capabilities, shortages of operational resources, and minimal community response to data correction invitations. Consequently, efforts to improve member competencies, innovations in public communication, and better resource allocation are essential to perfect the voter data updating process in future elections.